What Can Demographic–Economic Modeling Tell Us about the Consequences of Regional Decline?. (March 2018) - Batey, Peter W. J.
The aim of this article is to demonstrate how a particular modeling framework, based on extended input–output analysis, can be used to obtain a clearer understanding of the impact of regional decline of the effects of high, and rising, unemployment; of falling industrial final demand; of welfare payments; and of declining population. The activity–commodity framework used here provides a systematic way of adding demographic variables to the familiar Leontief interindustry model and the extended inverse derived from it provides a rich source of information about the interaction of demographic and economic change, expressed as demographic–economic and economic–demographic multipliers. Drawing on the author's research in the 1980s and 1990s, this article considers two empirical examples to show the framework's analytical value: a simple extended model is used to assess the distributional effects of welfare payments in a declining region; and a more elaborate version is linked to a set of regional labor market accounts, summarizing intercensal change in population and employment. This model is used to produce a comprehensive assessment of the effects of population and employment change in two UK regions, one a growing region (East Anglia) and the other a region in decline (Merseyside). In a final section, the benefits and limitations of the extended input–output modeling framework are discussed in comparison with some of the alternative modeling frameworks that are currently available.